The Monsters of Geoffrey Chaucer: The Miller in The General Prologue and the Miller in The Reeve’s Tale in The Canterbury Tales - Nazan Yıldız (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
The medieval universe was captivated by composite monsters like manticores and centaurs which adorned the margins of manuscripts and tales of medieval man. Medieval monsters were at the same time the Others of the society. Medieval Others are largely treated under the monster studies which begin with the dichotomy of “Us” (human beings) and “Them” (monsters). The Others of the Middle Ages were not limited to beasts, but embraced Saracens and Jews as the monstrous Others alongside heretics, pagans, homosexuals, lepers and witches. With their atypical social positions, millers were among those monstrous Others or “Them” of the Middle Ages as they could not be fitted into any of the three estates; namely the clergy, the nobility and the commoners. They were the unwanted upstarts and leading rebels of the Peasants’ Revolt of 1381. In accordance with their monstrous presence, the chronicles depicted the millers of the revolt with animal-like qualities. Similar to their historical counterparts, the most notable feature of Chaucer’s Miller in The Canterbury Tales is his animal-like appearance with a hairy face and a gigantic mouth. Aggressive and disruptive, rather than a human, the Miller looks like a wild animal bringing down doors-literally social boundaries- with his head. Parallel to the Miller in The General Prologue, the miller in The Reeve’s Tale possesses an animal-like appearance and a disobedient nature that grows into a threat to the social order. In this respect, this paper discusses Chaucer’s Miller in The General Prologue and his miller in The Reeve’s Tale as medieval monsters who are man-animal composites and defiant Others.